THE RELATION OF STUDENTS EMOTIONAL INTELLIGENCE (EQ) TO STUDENTS ACHIEVEMENT IN PHYSICS CLASS XII MAN I MEDAN ACADEMIC YEAR 2014/2015 - Laila Fauziyah; Sahyar Sahyar (UNIVERSITAS NEGERI MEDAN, 2017)
This study aims to determine how the relationship between students emotional intelligence to students achievementin physics class XII Science at MAN 1 Medan Academic Year 2014-2015. Sample in this study was class XII Science 5th at MAN 1 Medan was 40 respondents. The magnitude of emotional intelligence of students was measured using a questionnaire adapted from the questionnaire EQ MapTM made by Cooper, K and Sawaf and distributed directly to students obtained an average value for the emotional intelligence of students is 106 (good category). While the students learning outcomes in physics assessment tests obtained from physics problemobtained the average score was 69.13 (enough). Based on data analysis, the correlation coefficient between emotional intelligence of students to physics learning outcomes of students in class XII Science at MAN 1 Medan obtained rcountwas 0.76 and the coefficient of determination r2 was 57.76%. It was meant that there was a positive correlation between students emotional intelligence to students learning outcomes in physics, where students emotional intelligencefactor accounted for 57.76% of the increase in physics student learning outcomes. The hypothesis Ho was rejected at once receive Ha. There was a relationship between students emotional intelligence to students learning outcomes. Keyword: Emotional Intelligence, Learning Outcomes